The study of human life - Bennett, Joshua (Poet) (Penguin poets., 2022)
"A third collection that reveals an acclaimed poet further extending his range into the realm of speculative fiction, while addressing issues as varied as abolition, Black ecological consciousness, and the boundless promise of parenthood Across three sequences, Joshua Bennett's new book recalls and reimagines social worlds almost but not entirely lost, all while gesturing toward the ones we are building even now, in the midst of a state of emergency, together. Bennett opens with a set of autobiographical poems that deal with themes of family, life, death, vulnerability, and the joys and dreams of youth. The central section, "The Book of Mycah," features an alternate history where Malcolm X is resurrected from the dead, as is a young black man shot by the police some fifty years later in Brooklyn. The final section of The Study of Human Life are poems that Bennett has written about fatherhood, on the heels of his own first child being born last fall"--